The peculiarities of software localization for deaf and dull-hearing - Zajančkauskienė, Lina (Lietuvos matematikos rinkinys, 2010)
About thirty thousand Lithuanian people are deaf or dull of hearing for lots of reasons. 6272 persons are deaf – 3165 women and 3107 men. These problems are the main reason for these people to achieve degrees in studies and to live qualitative life. ICT should be that tool which could help people to learn and teach. There are some specialized computer programs, which are suitable to teach deaf and dull hearing person and to learn. One main problem – they are not Lithuanian. If we want to apply them in our learning process we should localize them. Sign languages, as well as spoken languages, are very different. So the main goal is to analyze how other colleagues localize these parts of software which is in sign languages and to give suggestions how to localize and maybe automate the localization of sign languages. The paper deals on their peculiarities of sign languages and how foreign colleagues apply software for deaf person.